2007
DOI: 10.1111/j.1365-2672.2006.03080.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a proteolytic enzyme derived from a Bacillus strain that effectively degrades prion protein

Abstract: Aims:  The purpose of this paper was to screen candidate bacterial strains for the production of proteases suitable for application to the degradation of pathogenic forms of prion protein (PrPSc). This paper describes the biochemical characteristics and proteolytic activity of the isolated protease. Methods and Results:  After screening more than 200 bacterial proteases for keratinolytic activity, we identified a Bacillus stain that produced a protease exhibiting high‐degradation activity against a scrapie PrP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 19 publications
1
35
0
1
Order By: Relevance
“…The temperature and pH optima in the presence of CaCl 2 were about 105°C and pH 6.5 (Šnajder et al, 2012). Purified keratinase from the strain MSK103 was also capable of degrading and decontaminating prion infected brain homogenate at 50°C without detergents or heat pretreatment (Yoshioka et al, 2007). The MSK103 enzyme had strong activity between 60-70°C and optimal pH was 9-10.…”
Section: Bio-safety On Infectious Prion Proteinsmentioning
confidence: 93%
See 1 more Smart Citation
“…The temperature and pH optima in the presence of CaCl 2 were about 105°C and pH 6.5 (Šnajder et al, 2012). Purified keratinase from the strain MSK103 was also capable of degrading and decontaminating prion infected brain homogenate at 50°C without detergents or heat pretreatment (Yoshioka et al, 2007). The MSK103 enzyme had strong activity between 60-70°C and optimal pH was 9-10.…”
Section: Bio-safety On Infectious Prion Proteinsmentioning
confidence: 93%
“…BA7, Actinomadura keratinilytica Cpt29 and Nocardiopsis sp. TOA-1 (Williams et al, 1990;Lin et al, 1992;Letourneau et al, 1998;Wang and Shih, 1999;Korkmaz et al, 2003;Gousterova et al, 2005;Mitsuiki et al, 2006;Yoshioka et al, 2007;Habbeche et al, 2014).…”
Section: Sources Of Keratinases Mesophilic Bacteriamentioning
confidence: 99%
“…Proteases may help degrading wrongly folded proteins. Yoshioka et al (2007) identified a protease-producing Bacillus strain that was capable of degrading scrapie PrP Sc . The protease (MSK 103) was also effective against dried PrP Sc .…”
Section: Proteases For Prion Degradationmentioning
confidence: 99%
“…Bacterial enzymes which effectively degrade prions have been identified, but they are most effective at high pH (10-12) and high temperature (50-60°C). 59,104 Microbiological consortia taken from the rumen and colon of cattle could degrade PrP Sc to undetectable levels within 20 hours under anaerobic conditions at 37°C, although infectivity remained. 60,105 Using an enzyme treatment, it may be possible to lower or eliminate the infectivity at identified or presumed CWD and scrapie 'hot spots' in captive and wild settings.…”
Section: Degradation and Mitigation Of Prions In The Environmentmentioning
confidence: 99%